The birth of the glorious Ming books, knowledge production and the formation of dynastic consciousness in the record of heroes and martyrs - Liu, Chiung-yun Evelyn (Tanjong Malim, 2020)
The birth of the glorious Ming books, knowledge production and the formation of dynastic consciousness in the record of heroes and martyrs by Liu, Chiung-yun Evelyn